STAKEHOLDERS’ KNOWLEDGE AND SKILLS ON CORE THEMES OF HOLISTIC SEXUALITY EDUCATION FOR MALAYSIAN CHILDREN WITH LEARNING DISABILITIES - Ng , Annie Mei Ling; Loh , Sau Cheong (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
A Holistic Sexuality Education (HSE) advocates that children, regardless of disabilities, learn about sexuality not only in formal education settings, but through multiple formal and informal channels. An effective HSE requires a collaborative effort involving various stakeholders to create a supportive environment. Despite documented challenges for adults to access and provide contemporary sexuality education to these children, fewer studies have empirically assessed their knowledge and skills. Thus, this study aimed to assess the current state of stakeholders' perceived levels of knowledge and skills regarding the core themes of Holistic Sexuality Education in Malaysia. An exploratory survey was conducted among 415 stakeholders with descriptive data analysis. The results revealed that the stakeholders demonstrated overall moderate levels of both knowledge and skills across the four targeted themes. However, performance varied among stakeholder groups and the four theme domains. The findings provided empirical input for the development of tailored content within a teaching guideline to ensure that the identified gaps are adequately addressed.